Mitochondrial DNA in Sepsis. Issue 4 (August 2017) - Harrington, John S.; Choi, Augustine M.K.; Nakahira, Kiichi
Abstract : Purpose of review: Our understanding of critical illness is transforming as we develop a better understanding of the impact pathogen-associated molecular patterns and damage-associated molecular patterns (DAMPs) have on the pathogenesis of disease. Of the known DAMPs, there is a growing interest in mitochondrial DNA (mtDNA) as a DAMP capable of propagating the inflammatory response seen in sepsis and other conditions. In this review, we describe the varying mechanisms by which mtDNA is translocated from mitochondria into cytosol and the extracellular space where it can illicit an inflammatory response. In addition, we present some of the most recent clinical studies to examine mtDNA in critical illness. Recent findings: Basic science research provides convincing data that mtDNA can influence the immune system through toll-like receptor 9 and inflammasomes. Clinical trials provide evidence that mtDNA is elevated in critically ill patients and is associated with mortality. Summary: Although mtDNA is a DAMP shown to be elevated in numerous conditions, the clinical ramifications of this finding remain elusive. Further work is needed to determine if mtDNA can be utilized as a biomarker of disease severity or mortality.